Symbolic domination in the neoliberal city: space, class, and residential stigma. Issue 4 (21st April 2022) - Otero, Gabriel; Méndez, María Luisa; Link, Felipe
ABSTRACT: This study examines how perceptions of residential reputation and stigma vary according to differences in social class and spatial structures. The focus of our inquiry is the city of Santiago, Chile – a highly segregated city in Latin America. We suggest that residential stigma is the focus of a larger assemblage of material and non-material marginalization; it is a point of convergence of multiple forms of social stratification. We combine a representative survey of 600 residents with geo-referenced census data, building composite measures to represent concrete class and spatial structures using clustering techniques. Results reveal that living in more affluent segregated areas is associated with a better perceived residential reputation, whereas perceived residential stigma is greater in geographical areas with a high concentration of poverty, land devaluation, population density, and overcrowding, regardless of whether these areas present high levels of criminality. Interestingly, when we include social class along with the spatial structure, the former loses significance as a predictor of both perceived residential reputation and stigma. The spatial structure therefore goes some way toward mediating the relationship between class and perceived residential reputation. This suggests the need for public policies designed to reduce the current symbolic domination that exists in Santiago.